Slang Words Translation in Hit Man Movie - Wahyuningsih, Neneng Sri; Pratiwi, Navillia Gita (e-LinguaTera, 2025)
This study examines how the Hit Man movies translations of slang terms were done. This study aims to identify the translation procedures utilized in translating the various slang word types contained in the film by analyzing the types of slang words employed. The data in this study are described and explained through the use of qualitative approaches and document analysis. The researcher employed both the theory of Mona Bakers (2018) translation technique and the theory put forward by Allan and Burridge (2006) regarding the types of slang words to examine the word usage. 18 data were categorized into different slang word categories in this study. There are four different kinds of translation strategies available at the moment. for slang words we only found two types with the same number, nine for the fresh and creative slang type and nine for the flippant slang type. The most popular translation method is neutral or less expressive translation.